Different training loads partially influence physiological responses to preparation period in basketball - Ferioli, D.; Bosio, A.; La Torre, A.; Carlomagno, D.; Connolly, D. R.; Rampinini, E. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to compare the session rating of perceived exertion training load (sRPE-TL), training volume (TV), and the changes in physical fitness between professional (n = 14) and semiprofessional (n = 18) basketball players during the preparation period. Furthermore, relationships between sRPE-TL and TV with changes in physical fitness level were investigated. The players performed the Yo-Yo intermittent recovery test—level 1 (Yo-Yo IR1) before and after the preparation period. In addition, physiological responses to a standardized 6-minute continuous running test (Mognoni's test) and to a standardized 5-minute high-intensity intermittent running test (HIT) were measured. Session rating of perceived exertion-TL and TV were greater for professional (5,241 ± 1787 AU; 914 ± 122 minutes) compared with semiprofessional players (2,408 ± 487 AU; 583 ± 65 minutes). Despite these differences, Yo-Yo IR1 performance improvements (~30%) and physiological adaptations to the Mognoni's test were similar between the 2 groups. Furthermore, physiological adaptations to HIT were slightly greater for professional compared with semiprofessional players; however, the magnitude of these effects was only small/moderate. No clear relationships were found between sRPE-TL and changes in Yo-Yo IR1 performance and Mognoni's test (r s ± 90% confidence interval [CI]: Yo-Yo IR1, 0.18 ± 0.30; Mognoni's test, -0.14 ± 0.29). Only moderate relationships were found between sRPE-TL and changes in HIT (r s ± 90% CI: [La-], -0.48 ± 0.23; [H+], -0.42 ± 0.25). These results raise doubts on the effectiveness of using high sRPE-TL and TV during the preparation period to improve the physical fitness level of players. The Yo-Yo IR1 seems to be sensitive to monitor changes induced by the preparation period; however, its use is not recommended to discriminate between adult basketball players of different competitive level.